Process Migration: Controlling Application and Resource Dynamics by Combining Computation, Communication and Memory Metrics - Graebin, Lucas; Righi, Rodrigo da Rosa; Navaux, Philippe Olivier Alexandre (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2011)
In this paper we present MigBSP, a rescheduling model that acts on Bulk Synchronous Parallel applications. It combines the metrics Computation, Communication and Memory to make migration decisions on Computation Grids. MigBSP also offers efficient adaptations to reduce its own overhead. Additionally, MigBSP is infrastructure and application independent and tries to handle dynamicity on both levels. MigBSP’s results show performance gains of up to 16% on dynamic environments while maintaining a small overhead when migrations do not take place.